A history of the Xhosa, c1700-1835 - Peires, J B (Jeffrey B) (Rhodes University, Faculty of Humanities, Department of History, 1977)
The boundaries of the territory occupied by the Xhosa fluctuated considerably, but in the period 1700-1835 they did not often extend west of the Sundays River, or east of the Mbashe River, along the coastal strip which separates the escarpment of South Africa's inland plateau from the Indian Ocean. It is an area of temperate grassland, permitting the cultivation of cereals and light crops, such as maize, millet, tobacco and pumpkins but better suited to stock-farming than intensive agriculture.
Keywords: Xhosa (African people) History 18th century; Xhosa (African people) History 19th century; Xhosa (African people) Religion; Xhosa (African people) Economic conditions; Phalo kaTshiwo; Ngqika kaRarabe; Maqoma